Seizure occurrences among hypoglycemic patients in the emergency department - Seigo Urushidani; Mao Tanabe; Kwangsoo Baek; Koki Miyaguchi; Tetsunori Ikegami (Acute Medicine & Surgery, 2024)
Abstract Aim Symptomatic hypoglycemia is a common problem in the emergency department (ED). However, without appropriate recognition and management, hypoglycemia remains a potentially fatal condition. The cause of sudden death associated with hypoglycemia might be attributed to cardiac arrhythmias and hypoxia with seizures. Despite advances in diabetes mellitus management and social background, the frequency and characteristics of patients with hypoglycemia‐related seizures have remained unknown. Hence, our study aimed to investigate the frequency and characteristics of patients with hypoglycemia presenting with seizures in the ED. Methods This retrospective observational study was conducted in a single tertiary care center. Patient information was retrieved from the final diagnostic records in the ED. We reviewed all medical records and included patients with symptomatic hypoglycemia aged 16 years or older. The primary outcome was the frequency of seizures in patients with hypoglycemia. We also compared the initial blood sugar levels of the patients with and without seizures. Results We included a total of 380 patients (median age, 72 years, IQR 64–80 years; median initial blood sugar, 34 mg/dL, IQR 24–46; 62.9% male). Nineteen of 380 patients (5.0%) had seizures. Although 16 of the 19 patients had diabetes mellitus, none of the 19 patients had a history of epilepsy. The initial blood sugar levels of the patients with and without seizures were not significantly different (p = 0.97). Conclusion Approximately 5% of the patients with hypoglycemia presented with seizures. Blood glucose levels of hypoglycemic patients with and without seizures did not differ.